Counseling services across public primary schools in Dar es Salaam: An exploratory study - Almasi, Mustapha; Tarimo, Theresia; Machumu, Haruni (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
From the perspective of counseling psychology, counseling is important in the overall development of school children. Thus, it should be provided to all learners. However, this is not the current reality in Tanzanian primary schools. This study explored the provision of counseling services and strategies applied by the teacher-counselors in selected primary schools in Tanzania. Data were collected through interviews with five teacher counselors across five schools. The findings showed that counseling services offered predominantly were individual, developmental, academic, and group counseling. The counseling services targeted personal pupils’ problems, such as nervousness, low achievements, and social-related problems. Mainly, four strategies were used in the study area: self-disclosure, summarizing and reframing, constructive confrontation, and person-centered strategy. As such, counseling services should be integrated into the overall school development plan, and teachers should effectively utilize demonstrated strategies to positively impact pupils' general development.